Paper Bag Production Using Banana Stem Via Kraft Pulping Process - Zairul Adli, Muhammad Hazim; Mohd Sharil, Muhammad Aiman; Nawi, Adnin Afifi (Multidisciplinary Applied Research and Innovation, 2023)
The banana plant supplies us with numerous polymers such as cellulose, hemicellulose, pectin, and lignin, which offer fibres with high mechanical qualities in addition to the abundant nutrient-rich bananas. Recently, the planting of banana trees is increasing which lead to an increase in the waste disposal of banana stems. Banana is an annual crop and it generates a huge quantity of fibrous material as waste from its leaves and stem; for every 60 kg of banana grown, 200 kg of the waste stem is generated. This project aims to produce paper by using the banana stem as non-wood raw material by using the kraft pulping method. Banana stem from jackfruit banana tree, kapas banana tree and nipah banana tree were obtained from banana farm around Kampung Parit Besar, Muar, Johor. The stem from each aforementioned banana tree is the main materials in this project to produce paper by the kraft pulping method as mentioned and finally analysed in term of absorbency, ash content and moisture content. The findings of this project can be seen from the two phases of an experiment conducted where the papers from the respective phases differ from the other. The differences detected in the first phase are the papers are thick, hard and have a rough surface while in the second phase, the papers are thinner, softer and have smoother surfaces. To conclude the best paper produced compared to the standard used is Kapas B which was produced in the second phase of production. Kapas B is the best overall as it conquers ash content and moisture content analysis while also being the third best in terms of absorbency which is not that far from the standard. The suggestion on the best amount of pulp to be used is 25-30g.